IoT-Enabled Monitoring and Methane Energy Forecasting in Tofu Waste Biogas Systems for Electricity Generation - Fitri Oktafiani; Sigit Kusuma Wijaya; Al Mutaqim; Ferdi Bagus Purnomo; Hamsir Hamsir; Riza Hadi Saputra (TEPIAN, 2026)
This study presents the development of an Internet of Things based monitoring system and methane energy forecasting for biogas production from tofu wastewater in Somber, Balikpapan. A 1000 L anaerobic biodigester was installed at a home scale tofu industry to process liquid tofu waste through anaerobic fermentation. The monitoring system utilized three ESP32 microcontrollers integrated with MQ-4 methane sensors, DHT11 temperature–humidity sensors, BMP180 pressure sensors, and ultrasonic level sensors. Data were transmitted every 8–10 seconds to Google Spreadsheet via Wi-Fi for real time monitoring. Observations were conducted over a 21-day fermentation period. The results show that methane concentration increased from approximately 4,720–4,810 ppm on day 13 to 5,000–5,050 ppm on day 21. Humidity remained relatively stable between 93.6% and 94.2%, while temperature ranged from 31.5°C to 42.6°C. The average methane quantity was estimated at 1.42 × 10⁷ mol, corresponding to a theoretical energy potential of approximately 3.17 × 10⁶ kWh. These results indicate strong potential for small scale biogas based power generation.